Articulate storyline 3 based interactive media to explore mathematical communication ability: development and implementation - Ratnaningsih, Nani; Said Husain, Sharifah Kartini; Hetty Patmawati; Sukirwan, S.; Hidayat, Edi; Nisa Sri Romdiani (Taylor's University Sdn Bhd, 2024)
The purpose of this research is to develop articulate storyline 3 based interactive media to explore mathematical communication ability. The method used was research and development (R and D) with the ADDIE development model including the stages of analysis, design, development, implementation, and evaluation. Data collection techniques used tests, observations, questionnaires, and interviews. The results found that articulate storyline 3-based interactive media is feasible and effective to use to explore mathematical communication ability. Mathematical communication ability reached completion, and the use of articulate storyline 3 had a strong effect. Students' response to the use of articulate storyline 3 interactive media is very good. This is because articulate storyline 3 interactive media has the advantage of various features that present contextual problems that are related to everyday life. Students explore mathematical communication skills through the problems presented and videos of social arithmetic material. This research has implications for improving mathematical communication skills and learning motivation, students can learn independently regardless of space and time and do not have to be under the guidance of a teacher.